2012
DOI: 10.1590/s1413-81232012000700009
|View full text |Cite
|
Sign up to set email alerts
|

Motivos e circunstâncias para o aborto induzido entre mulheres vivendo com HIV no Brasil

Abstract: Motivos e circunstâncias para o aborto induzido entre mulheres vivendo com HIV no BrasilMotives and circumstances surrounding induced abortion among women living with HIV in Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
0
6
0
11
Order By: Relevance
“…Some relate to seropositive status, such as the fear of vertical transmission, fear of not being able to raise the child due to one's health condition, and the impediment to breastfeeding in a society that values it as affirmation of one's identity as a woman and mother. In addition, the relationship with the male partner and his support, as well as that of the immediate family, are other fundamental elements in making the decision 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Some relate to seropositive status, such as the fear of vertical transmission, fear of not being able to raise the child due to one's health condition, and the impediment to breastfeeding in a society that values it as affirmation of one's identity as a woman and mother. In addition, the relationship with the male partner and his support, as well as that of the immediate family, are other fundamental elements in making the decision 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…As mulheres infectadas neste período começam a se beneficiar da política pública voltada para oferta de testagem no pré-natal, implementado como forma de ampliar e antecipar o diagnóstico entre mulheres e, principalmente, para reduzir a transmissão do HIV para o recém-nascido de uma portadora. Há semelhança entre as trajetórias das entrevistadas e aquelas identificadas em estudos anteriores 11,14,18 e posteriores 15 , sugerindo uma persistência na dinâmica da vulnerabilidade das mulheres ao HIV que não foi afetada pelo tempo decorrido entre a realização das entrevistas e a atual análise.…”
Section: Discussionunclassified
“…Assim, o número de mulheres que em algum momento foram trabalhadoras sexuais confirma a vulnerabilidade deste grupo ao HIV; ao mesmo tempo, a análise das suas trajetórias aponta que esta circunstancia nem sempre se constitui como uma identidade pessoal ou profissional, como já apontado em outros estudos 14 . Se o perfil de baixa escolaridade, precária inserção laboral e violência na vida caracteriza as mulheres vivendo com HIV/aids desde o início da epidemia no país, a redução daquelas que tiveram diagnóstico em função dos sintomas dos parceiros, e o aumento proporcional das que conheceram a sua sorologia positiva no pré-natal aponta para o efeito da oferta de testagem nesta ocasião ou no parto, tornada política pública desde meados dos anos 90 20 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A research on the decisions of women concerning unsafe abortion showed that the partner, also responsible for the pregnancy, was the person who influenced for abortion in 64% of the occasions, followed by friends and the mother of the young women 24 . The woman herself can also seek for opinions from people close to her to help in the decision, and also count on the experiences of other women with abortions 23,25 . The confidence in people, who are not health professionals in most cases, prevents the woman from seeking opinions of qualified people.…”
Section: Discussionmentioning
confidence: 99%